Establishment of the Virtual Prototyping of Angular Transmission Error of RV Reducer based on Multi-body Dynamics Simulation - Chang Anquan; Zhang Yinghui; He Weidong; Wang Xiaoyu (Jixie chuandong)
In order to study the influence of modification of cycloid gear and bearing clearance on angular transmission error of RV reducer,based on the multi-body dynamics simulation technology,multi-body contact between gears is established by combining with the most advanced mixed contact checking algorithm rely on relative coordinate contact configuration space method and boundary box method,furthermore the spring force element is used to eliminate the redundant constraints in the dynamic simulation model,at the same time the bearing clearance is introduced,at last the dynamic simulation model of RV reducer containing the cycloid gear modification and bearing clearance is established. Then the angular transmission error of RV reducer under the condition of special tooth profile modification of cycloid gear and different quantity of bearings clearance are checked by multi-body dynamics simulation,which providing a new modeling ideas and methods for studying the effect of cycloid gear profile modification and bearing clearance on angle transmission of RV reducer with multi-body dynamics simulation.